Is President Obama's Race Chronically Accessible? Racial Priming in the 2012 Presidential Election. (1st October 2016) - Luttig, Matthew D.; Callaghan, Timothy H.
Abstract : A vast literature indicates that racial animosity has a pervasive influence on the public's evaluations of U.S. President Barack Obama. Can political communications enhance and/or defuse the link between White Americans' racial attitudes and evaluations of Barack Obama? In this article, we report the results of an experiment conducted in the midst of the 2012 presidential campaign which examines the effect of political rhetoric on the extent to which evaluations of Barack Obama are racialized. Drawing from research on attitude strength and pretreatment effects in experimental studies, we argue that the use of racial appeals in the pretreatment environment and the strength of citizens' preexisting attitudes toward the incumbent president may produce a downward bias in average estimates of racial priming effects toward President Obama. After accounting for individual differences in the propensity to form strong attitudes with need to evaluate, we observe substantial effects of campaign rhetoric in priming racial attitudes toward President Obama, especially among individuals who are low in the need to evaluate and who tend to have more malleable political attitudes. We conclude by discussing implications for research on racial priming and the politics of racial intolerance in evaluations of Barack Obama.